Investigation of calcified atherosclerotic plaques on panoramic radiographs (Annals of Medical Research, 2024)
Aim: This study aims to determine the prevalence of calcified atherosclerotic plaques (CAPs) incidentally encountered in the carotid artery within panoramic radiography (PR) images.Materials and Methods: A total of 1,200 patients (646 females, 554 males) referred to our clinic in January 2022 and January 2023 was included. CAPs within PRs were assessed, with data stratified by gender, age, and systemic conditions. Statistical analysis employed descriptive statistics and chi-square tests (p
Keywords: Calcification; Carotid artery; Panoramic radiography; Soft tissue